Estudio comparativo de los procesos químico y biológico para elaborar silages de pescado - Rivas Ríos, Daysy Virginia (2011)
This research was conducted at the Laboratory of Technology and Processing of aquatic organisms from the Faculty of Agropecuary Sciences, University of Machala, located at Km 5 ½ via a Pasaje, El Oro province, with the purpose of preparing silage by two technologies, biological and chemical from fish Selene peruviana (face), and in turn determine which of these two methods is appropriate for a higher percentage of protein end product developed or silage, also based in organoleptic qualities to ensure their conservation and quality. Was used as starting material for fish Selene peruviana (face), including the viscera. To be able to get the silage had to perform the following steps which are: Washing, Gutted, Scalding, grinding, packaging and addition of molasses, inoculation of bacteria and acids, Homogenization and sealing of the product, while taking into account their proper controls for temperature and pH concerns throughout the process. The samples obtained in the two treatments were tested in the analysis comprise organoleptic odor, color and texture, which we determine their condition and quality. In the same way all the samples are analyzed for evidence dietetics in order to obtain the percentages of protein, ash and moisture.